Risk of low Apgar scores and socioeconomic status over a 30-year period. (April 2014) - Odd, D.; Lewis, G.; Gunnell, D.; Rasmussen, Finn
Abstract Objective: The aim of this study was to investigate the stability of associations between social factors, as assessed by maternal occupation and education, and poor birth condition (an Apgar score of below 7 at 1 and 5 minutes) over a 30-year period in Sweden. Methods: The dataset was based on infants born in Sweden between 1973 and 2002. Poor birth condition was defined as an Apgar score below 7 at 1 and 5 minutes. Logistic regression was used to investigate the association of between socioeconomic status and poor birth condition. Results: In the adjusted model, mothers in non-manual occupations (OR 0.91 (0.88, 0.95)) or with higher educational status (OR 0.88 (0.84, 0.93)) were less likely to have an infant born in poor condition than the reference group. Limiting the analysis to the last decade showed less evidence for an association (OR 0.94 (0.86, 1.02) and OR 0.94 (0.82, 1.09), respectively). Conclusions: While maternity, delivery and child healthcare are free of charge in Sweden, poor birth condition was more common among infants of mothers in manual occupations or low levels of education. However, this association appeared to attenuate over the calendar period studied.